Prevalence of Coaddictions and Rate of Successful Treatment Among a French Sample of Opioid-Dependent Patients With Long-Term Opioid Substitution Therapy: The OPAL Study - Grall-Bronnec, Marie; Laforgue, Edouard-Jules; Challet-Bouju, Gaëlle; Cholet, Jennyfer; Hardouin, Jean-Benoit; Leboucher, Juliette; Guillou-Landréat, Morgane; Victorri-Vigneau, Caroline (Frontiers in Psychiatry, 2019)
Background: Opioid use disorder (OUD) is a worldwide major health concern due to increased early mortality, and morbidity. Opioid Substitution Therapy (OST) is approved in the context of a global OUD treatment, in conjunction with psychosocial interventions. Many factors can explain why unsuccessful treatment rates remain high. Whilst the phenomenon of addiction switching is often proposed, it is not known whether this also includes gambling addiction. The primary objective of the OPAL study was to determine the prevalence of co-addictions, including problem gambling, among patients with OUD treatment (OUDT). Secondary objectives were to assess the rate of unsuccessful OUDT and to characterize the associated factors. Methods: For this observational transversal multicenter study, patients with OUDT including OST for at least 6 months were recruited. Clinical assessment was based on a clinically structured interview and a set of self-reported questionnaires. Co-addictions were screened using the Fagerstöm, the CRAFFT and the Lie/Bet questionnaires. Unsuccessful OUDT was defined as the persistence of opioid use and/or the worsening of another substance use or gambling practice. After a descriptive analysis, a multivariate analysis was performed to identify the factors associated with unsuccessful OUDT. Results: The sample consisted of 263 patients. Prevalence of co-addictions reached 97% of the sample. Problem gambling was associated with 10% of the patients. OUDT was considered as “Unsuccessful” for 60% of the patients. Associated factors included having drug-using friends, psychiatric and professional negative consequences related to opioid use, more than one OST prescribing physician and impulsivity, especially high scores for lack of premeditation and sensation seeking. Conclusions: This study provides further evidence of the need to consider co-addictions, and the usefulness of global addictive evaluations. Poor prognostic factors must alert the clinician to initiate more sustained care. Further implications are discussed.